Searching for predictive climate signals for river flows in the Lower Colorado River Basin of Texas - Anderson, Ronald, author; Rose, Bob, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2012)
The Highland Lakes are operated by the Lower Colorado River Authority (LCRA) in Texas to provide water supply to municipal, industrial, agricultural users and environmental flows for the river and Matagorda Bay. The Highland Lakes also provide for hydroelectric generation and recreation. The catchment area is in the Texas Hill Country, a region classified as the Edwards Plateau. Subject to extended droughts interrupted by intense rainfall, the region has the nickname of Flash Flood Alley. Precipitation in the region is understood to be influenced by oceanic conditions in the Pacific, Atlantic, and Gulf of Mexico. While the behavior of these global climate patterns is climatologically understood, finding strong skill in prediction of streamflows has been challenging. Identifying concurrent teleconnections, and to a lesser extend lagging indicators, is a critical first step for finding potential for predictors. Research efforts have often focused on predicting rainfall or climatic indexes. However, surface water managers need to relate predictions to streamflows. Climate indices can also be useful if they are hindcasted, enabling for relationships to the streamflow record to be established. Persistence is one of the strongest predictive indicators in the region, primarily through the winter season. Persistence is useful in short term predictions because it directly relates to streamflows and indirectly is influenced by teleconnection patterns. Therefore explicitly considering teleconnection patterns adds less incremental short term skill but potential benefit for longer term prediction. Use of persistence and ENSO forecasts are currently being used in water supply forecasts at the LCRA.
Irrigated agriculture responds to water use challenges
Predictive climate signals
Presented at Irrigated agriculture responds to water use challenges - strategies for success: USCID water management conference held on April 3-6, 2012 in Austin, Texas.